THE THEORETICAL FOUNDATIONS OF MAQAM AND MODE SYSTEMS IN EASTERN MUSIC - Ayubov Qobil Zoidovich (Western European Studies, 2025)
This study explores the evolution, theoretical foundations, and pedagogical significance of the maqam system in Eastern music. Over centuries, the concept of maqam expanded beyond a simple modal structure to include aesthetic, melodic, rhythmic, and stylistic dimensions. The research emphasizes the maqam as a system of pitch organization and its relationship to modal harmony, melodic contour, improvisation, and musical identity. Utilizing historical treatises, ethnomusicological analysis, and contemporary performance practices, the study demonstrates how the maqam system functions both as a theoretical framework and as a guide for performance in Central Asian and broader Eastern music traditions. The findings provide a comprehensive understanding of the maqam’s cultural, philosophical, and cognitive dimensions
Keywords: maqam; mode system; Eastern music theory